Democratizando a participação da sociedade civil: o caso do Conselho Estadual do Trabalho, Emprego e Geração de Renda no estado de Minas Gerais (CETER/MG) - Renata Chaves Azevedo (2006)
The vitality of this study is on the debates that emerged at the end of the twentieth century about the changings related to the crisis in the management structure of the Welfare State, that happened in the 1960s and 1970s. We can note a social mobilization towards a wider democratic process that questions the public management efficiency in reaching social and economic objectives. That process in Brazil was mainly during a period of dictatorial government. The civilian participation in public management is regarded as a mean to address and solve social and economic issues by the people who have experiencedthe nature of their actual needs as well as being part of the public decisions made. This study, done throughout 2004 and 2005, has as main objective understand the operational aspect of an organization that treats public management sharing as a priority, the Conselho Estadual do Trabalho, Emprego e Geração de Renda no Estado de MinasGerais (CETER/ MG). To gather the data, it was reserched documents and bibliography related to the issue, interviews with members of the board and participation in one of their meetings. Such methodology allowed us to conclude that the shared participation is happening, but in a very limited way. Those limitations are due to a resistance against leaving behind the vertical structure of decisions, interfering in the policies formulations and their practical use. We can notethat the autonomy and sharing structure are contradictory because there is not an actual reward of the government policies, but its combination with new laws, generating a different kind of management, but that doesnt contribute to widen democracy as expected.